The auditory template hypothesis: a review and comparative perspective. (February 2017) - Soha, Jill
Abstract : Studies of vocal development in the white-crowned sparrow, Zonotrichia leucophrys, and other songbirds led to Peter Marler's formulation of the auditory template hypothesis. According to this hypothesis, young songbirds possess an auditory template system that serves three functions in song learning: to focus attention on appropriate song models during the sensitive period, to facilitate memorization of these models, and later, to guide motor development of song during the sensorimotor phase. Marler postulated two types of innate templates: latent templates that require activation by external input, and preactive templates that do not. Here, I review experiments that examined the specifications of these templates in the white-crowned sparrow and suggest that this system also serves a fourth function, acting to shape the final repertoire at the end of song development. I then discuss the template system in a comparative context, first reviewing the influence of results from several species on the derivation of the auditory template hypothesis and then describing variation in several aspects of auditory templates across species. Finally, I address ways in which the template model can continue to be informative in the comparative study of song learning. Highlights: I review the functions of auditory templates in birdsong learning. Peter Marler postulated two types of innate templates: preactive and latent. White-crowned sparrow song learning illustrates these two types. I propose that templates also act late in development to shape the final repertoire. I discuss variation in auditory template systems across songbird species.